Cortical thickness and surface area correlates with cognitive dysfunction among first-episode psychosis patients. Issue 10 (7th June 2016) - Haring, L.; Müürsepp, A.; Mõttus, R.; Ilves, P.; Koch, K.; Uppin, K.; Tarnovskaja, J.; Maron, E.; Zharkovsky, A.; Vasar, E.; Vasar, V.
Abstract : Background: In studies using magnetic resonance imaging (MRI), some have reported specific brain structure–function relationships among first-episode psychosis (FEP) patients, but findings are inconsistent. We aimed to localize the brain regions where cortical thickness (CTh) and surface area (cortical area; CA) relate to neurocognition, by performing an MRI on participants and measuring their neurocognitive performance using the Cambridge Neuropsychological Test Automated Battery (CANTAB), in order to investigate any significant differences between FEP patients and control subjects (CS). Method: Exploration of potential correlations between specific cognitive functions and brain structure was performed using CANTAB computer-based neurocognitive testing and a vertex-by-vertex whole-brain MRI analysis of 63 FEP patients and 30 CS. Results: Significant correlations were found between cortical parameters in the frontal, temporal, cingular and occipital brain regions and performance in set-shifting, working memory manipulation, strategy usage and sustained attention tests. These correlations were significantly dissimilar between FEP patients and CS. Conclusions: Significant correlations between CTh and CA with neurocognitive performance were localized in brain areas known to be involved in cognition. The results also suggested a disrupted structure–function relationship in FEP patients compared with CS.